2001
DOI: 10.1038/sj.onc.1204479
|View full text |Cite
|
Sign up to set email alerts
|

TEL contacts multiple co-repressors and specifically associates with histone deacetylase-3

Abstract: TEL (Translocation ± ETS ± Leukemia or ETV 6) is disrupted by multiple chromosomal translocations in acute leukemia. The loss of heterozygosity at the TEL locus in leukemias and the hemizygous deletion of TEL that is observed in various tumors, suggests that TEL is a tumor suppressor. Overexpression of TEL alters cellular morphology and represses the expression of the matrix metalloproteinase stromelysin-1. Based on these studies, deletion analysis was used to de®ne the minimal repression domains of TEL. TEL-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 71 publications
2
70
0
1
Order By: Relevance
“…This region has been shown to recruit the corepressor N-CoR and histone deacetylase-3 (Guidez et al, 2000;Wang and Hiebert, 2001). We found that the region of TEL Cterminal of the HLH domain, which includes the CR domain, is also essential for TEL-AML1 to initiate progenitor B-cell expansion from HSC.…”
Section: Domain Analysis Of Tel-aml1 M Morrow Et Almentioning
confidence: 50%
“…This region has been shown to recruit the corepressor N-CoR and histone deacetylase-3 (Guidez et al, 2000;Wang and Hiebert, 2001). We found that the region of TEL Cterminal of the HLH domain, which includes the CR domain, is also essential for TEL-AML1 to initiate progenitor B-cell expansion from HSC.…”
Section: Domain Analysis Of Tel-aml1 M Morrow Et Almentioning
confidence: 50%
“…30,31 (iii) Acute leukemias with translocations involving TEL also showed an interference with the co-repressor N-CoR. 32 We found that overexpressed SKI inhibits RARa signaling in different cytogenetic subgroups of AML. As described for leukemias (i-iii), where HDAC inhibitors impaired the repression of differentiation, we could show that the HDAC inhibitor VPA partially reverted the effect of overexpressed Ski.…”
Section: Discussionmentioning
confidence: 86%
“…The finding that the CFS variant of TEL-TRKC but not the L form interferes with the expression of Flk1 provides a lead in how this selectivity might arise, as does the known activity of central region of TEL (encoded by exon 5) to recruit transcriptional corepressors (40)(41)(42)(43). CFS TEL-TRKC protein mainly localizes in the cytoplasm (data not shown), and, therefore, any transcriptional deregulating activity would presumably be indirect, e.g., by sequestering components in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%